Component-Based Software Engineering 11th International Symposium, CBSE 2008, Karlsruhe, Germany, October 14-17, 2008, Proceedings - Chaudron, Michel R. V.; Szyperski, Clemens; Reussner, Ralf H. (Programming and Software Engineering, 2008)
This book constitutes the refereed proceedings of the 11th International ACM SIGSOFT Symposium on Component-Based Software Engineering, CBSE 2008, held in Karlsruhe, Germany in October 2008. The 20 revised full papers and 3 short papers presented were carefully reviewed and selected from 70 submissions. The papers feature new trends in global software services and distributed systems architectures to push the limits of established and tested component-based methods, tools and platforms. The papers are organized in topical sections on performance engineering; extra-functional properties: security and energy; formal methods and model checking; verification techniques; run-time infrastructures; methods of design and development; component models.